WINCENTY SKRZETUSKI O POTRZEBIE ORAZ ZMIANACH W PRAWIE I USTROJU DOBY STANISŁAWOWSKIEJ - Organiściak, Wojciech (Zeszyty Prawnicze, 2016)
WINCENTY SKRZETUSKI ABOUT NECESSITY ALSO FOR A CHANGE OF LEGAL SYSTEM AND POLITICAL SYSTEM OF THE TIMES STANISŁAW AUGUST REIGN (1764-1795) Summary Wincenty Skrzetuski, in his work The Political Law of the Polish Nation, when discussing the issue of the functioning of the political system of he gentry Republic, presented a liberum veto, a short draft which he considered one of the most disastrous mechanisms of the abuse of citizen-ship freedom for Poland. Polish piarist made interesting historical digressions which showed some of the weak points of the solutions functioning in the parliamentary practice of the First Republic of Poland. Wincenty Skrzetuski, discussing a procedure of parliamentary sessions, ammended in the period of Stanisław August, did not always clearly emphasise the solutions aiming at simplification and acceleration of the course of the parliamentary sessions. It needs to be emphasized that describing the problem of parliamentary clearances, he referred to disastrous parliamentary practices and was in line with some drafters of the reforms in the gentry Republic of Poland who demanded radical changes in the clearance procedure or even its total abolishment. The opinions and viewpoints presented by Skrzetuski allow for ascribing him to the group of the continuators of the work by Stanisław Konarski. Wincenty Skrzetuski’s attitudes to law and critical of the legal system of his times, he postulated abolition of severe penalties in favour of creating conditions ascertaining that a punishment is truly carried out. This Piarist scholar followed the Renaissance views that laws should be written in a concise, clear and comprehensive language, and be free from any contradictions. Skrzetuski in your “Speeches on the main political matters” postulated an urgent and unconditional abolition of torture. Many of his arguments related almost directly to Cesare Beccaria’s “On crimes and punishments” or derived from the thoughts of eminent thinkers like Montesquieu and Rousseau.